The Clinical Genome Resource (ClinGen) Familial Hypercholesterolemia Variant Curation Expert Panel consensus guidelines for LDLR variant classification - Chora, Joana R; Iacocca, Michael A; Tichý, Lukáš; Wand, Hannah; Kurtz, C Lisa; Zimmermann, Heather; Leon, Annette; Williams, Maggie; Humphries, Steve E; Hooper, Amanda J; Trinder, Mark; Brunham, Liam R; et al. (Genetics in medicine, 2022)
PURPOSE: In 2015, the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) published consensus standardized guidelines for sequence-level variant classification in Mendelian disorders. To increase accuracy and consistency, the Clinical Genome Resource Familial Hypercholesterolemia (FH) Variant Curation Expert Panel was tasked with optimizing the existing ACMG/AMP framework for disease-specific classification in FH. In this study, we provide consensus recommendations for the most common FH-associated gene, LDLR, where >2300 unique FH-associated variants have been identified. METHODS: The multidisciplinary FH Variant Curation Expert Panel met in person and through frequent emails and conference calls to develop LDLR-specific modifications of ACMG/AMP guidelines. Through iteration, pilot testing, debate, and commentary, consensus among experts was reached. RESULTS: The consensus LDLR variant modifications to existing ACMG/AMP guidelines include (1) alteration of population frequency thresholds, (2) delineation of loss-of-function variant types, (3) functional study criteria specifications, (4) cosegregation criteria specifications, and (5) specific use and thresholds for in silico prediction tools, among others. CONCLUSION: Establishment of these guidelines as the new standard in the clinical laboratory setting will result in a more evidence-based, harmonized method for LDLR variant classification worldwide, thereby improving the care of patients with FH.
Keywords: genetické testování; Genetic Testing; Genetic Variation; Genomics; lidé; ACMG/AMP; Genome, Human; genom lidský; Hyperlipoproteinemia Type II; LDLR; genetická variace; Familial hypercholesterolemia; hyperlipoproteinemie typ II; Variant classification; ClinGen; genomika; Humans